Diversification in Hawaiian long-legged flies (Diptera: Dolichopodidae: Campsicnemus): biogeographic isolation and ecological adaptation - Goodman, Kari Roesch; Evenhuis, Neal L; Bartošová-Sojková, Pavla; O'Grady, Patrick M (Molecular phylogenetics and evolution, 2014)
Flies in the genus Campsicnemus have diversified into the second-largest adaptive radiation of Diptera in the Hawaiian Islands, with 179 Hawaiian endemic species currently described. Here we present the first phylogenetic analysis of Campsicnemus, with a focus on the Hawaiian fauna. We analyzed a combination of two nuclear (CAD, EF1α) and five mitochondrial (COI, COII, 12S, 16S, ND2) loci using Bayesian and maximum likelihood approaches to generate a phylogenetic hypothesis for the genus Campsicnemus. Our sampling included a total of 84 species (6 species from Europe, 1 from North America, 7 species from French Polynesia and 70 species from the Hawaiian Islands). The phylogenies were used to estimate divergence times, reconstruct biogeographic history, and infer ancestral ecological associations within this large genus. We found strong support for a South Pacific+Hawaiian clade, as well as for a monophyletic Hawaiian lineage. Divergence time estimates suggest that Hawaiian Islands were colonized approximately 4.6 million years ago, suggesting that most of the diversity within Campsicnemus evolved since the current high islands began forming ∼5 million years ago. We also observe a novel ecotype within the Pacific Campsicnemus; a widespread obligate water-skating form that has arisen multiple times across the Pacific Islands. Together, these analyses suggest that a combination of ecological, biogeographic and temporal factors have led to the impressive diversity of long-legged flies in Hawaii and elsewhere in the Pacific.
Keywords: Models, Genetic; Polynesia; Sequence Analysis, DNA; modely genetické; Havajské ostrovy; biologická evoluce; Hawaiian Islands; Adaptive radiation; Bayes Theorem; Historical biogeography; Dolichopodidae; Biological Evolution; DNA, Mitochondrial; pravděpodobnostní funkce; Polynésie; Bayesova věta; Ecotype; zvířata; mitochondriální DNA; fylogeneze; Divergence dating; sekvenční analýza DNA; Hawaii; Diptera; Phylogeny; Likelihood Functions; Animals